Magnetic liquid as well as preparation method and application thereof

By using rod-shaped magnetic nanoparticles and specific surfactants in the preparation process of magnetic liquids, the problem of high demagnetization effect of existing magnetic liquids is solved, and higher coercive force and stability are achieved.

CN119601338APending Publication Date: 2025-03-11TSINGHUA UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510128132.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The demagnetization effect of existing magnetic liquids is high, resulting in unstable magnetic properties.

Method used

Rod-shaped magnetic nanoparticles are used to combine raw materials such as activators, long-chain fatty acids and short-chain fatty acids to prepare magnetic liquids through specific mixing and ball milling processes to improve their coerciveness and reduce the demagnetization effect.

Benefits of technology

It significantly improves the coercive force of the magnetic liquid, reduces the demagnetization effect, and makes it more stable in the external fluctuating magnetic field, with good stability and magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of materials, and particularly relates to magnetic liquid and a preparation method and application thereof. The magnetic liquid comprises the following raw materials in parts by mass: 25-30 parts of rodlike magnetic nanoparticles, 1-4 parts of an activating agent, 15-20 parts of a surfactant and 50-75 parts of base carrier liquid. The magnetic liquid disclosed by the invention has the beneficial effects that the magnetic liquid is prepared from the rod-shaped magnetic nanoparticles, has relatively high coercive force, can reduce the demagnetization effect, can relatively stably respond to an external fluctuating magnetic field, and has good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material technology, and specifically relates to a magnetic liquid and a preparation method and application thereof. Background Art

[0002] Magnetic liquid is a functional magnetic material formed by uniformly and stably dispersing magnetic nanoparticles coated with surfactant in a base carrier liquid. It has both the fluidity of liquid and the magnetic properties of solid. Due to its excellent magnetic response performance and fluidity, it is widely used in mechanical sealing, vibration reduction and drag reduction, biomedicine, surface lubrication and other fields.

[0003] The demagnetization effect is one of the important indicators for evaluating the magnetic properties of magnetic liquids. It refers to the phenomenon that the magnetism of the material gradually weakens or disappears after the external magnetic field is removed. The demagnetization effect is determined by factors such as particle morphology, particle size, and crystal structure. The coercive force can reflect the demagnetization effect of magnetic nanoparticles, and can also reflect the stability of the material against magnetic field fluctuations. The higher the coercive force, the lower the demagnetization effect. At the same time, it can be said that the magnetic properties of the magnetic liquid are good and the magnetic liquid is more stable. At present, the coercive force of magnetic liquids is generally between 10-50Oe. The coercive force is low and the demagnetization effect is obvious. Summary of the invention

[0004] The present application provides a magnetic liquid and a preparation method and application thereof, aiming to solve the problem of high demagnetization effect of existing magnetic liquids.

[0005] In a first aspect, the present application provides a magnetic liquid, comprising the following raw materials in parts by weight: 25-30 parts of rod-shaped magnetic nanoparticles, 1-4 parts of an activator, 15-20 parts of a surfactant, and 50-75 parts of a base carrier liquid.

[0006] The magnetic liquid described in the present application is prepared using rod-shaped magnetic nanoparticles, has a high coercive force, can reduce the demagnetization effect, can respond to external fluctuating magnetic fields more stably, and has good stability.

[0007] According to some embodiments of the magnetic liquid described in the present application, the rod-shaped magnetic nanoparticles include one or more of Fe3O4 nanoparticles, γ-Fe2O3 nanoparticles and MFe2Ox nanoparticles, where 2≤X≤4, and M includes one or more of Mn, Co, Ni, Cu, Cd, Pb, Sn, Ca, Sr, Ba and Mg.

[0008] According to some embodiments of the magnetic liquid described herein, the activator includes one or more of carbide, nitride and silicon dioxide.

[0009] According to some embodiments of the magnetic liquid described in the present application, the surfactant includes a long-chain fatty acid having a carbon number greater than or equal to 10 and a short-chain fatty acid having a carbon number less than 10.

[0010] According to some embodiments of the magnetic liquid described in the present application, the base carrier liquid includes a fat-soluble liquid.

[0011] According to some embodiments of the magnetic liquid described in the present application, the long-chain fatty acid includes one or more of oleic acid, linoleic acid, stearic acid, palmitic acid and lauric acid.

[0012] According to some embodiments of the magnetic liquid described in the present application, the short-chain fatty acid includes one or more of acetic acid, propionic acid, butyric acid and octanoic acid.

[0013] According to some embodiments of the magnetic liquid described in the present application, the carbide includes one or more of silicon carbide, calcium carbide and carbon nanotubes.

[0014] According to some embodiments of the magnetic liquid described in the present application, the nitride includes one or more of silicon nitride, aluminum nitride and iron nitride.

[0015] According to some embodiments of the magnetic liquid described in the present application, the base carrier fluid includes kerosene and / or motor oil.

[0016] According to some embodiments of the magnetic liquid described in the present application, the volume ratio of the long-chain fatty acid to the short-chain fatty acid is 1:(1-5).

[0017] The second aspect of the present application provides a method for preparing the magnetic liquid according to the first aspect of the present application, comprising the following steps: (1) performing a first mixing of rod-shaped magnetic nanoparticles, an activator, and a first solvent to obtain activated rod-shaped magnetic nanoparticles; (2) performing a second mixing of the activated rod-shaped magnetic nanoparticles, the surfactant and the second solvent in step (1) to obtain modified rod-shaped magnetic nanoparticles; (3) The modified rod-shaped magnetic nanoparticles and a base carrier liquid are mixed and ball milled to obtain a magnetic liquid.

[0018] The magnetic liquid described in the present application introduces an activator during the preparation process, which can prevent the magnetic nanoparticles from being oxidized and avoid oxidative demagnetization caused by the external environment, while providing more surface sites for better adsorption of surfactants. In addition, during the preparation process of the magnetic liquid described in the present application, long-chain fatty acids and short-chain fatty acids simultaneously coat the magnetic nanoparticles, which helps to better disperse the magnetic nanoparticles into the base carrier liquid to form a stable magnetic liquid.

[0019] According to some embodiments of the method for preparing the magnetic liquid described in the present application, in step (1), the temperature of the first mixing is 25-40° C., and the time of the first mixing is 1-60 min.

[0020] According to some embodiments of the method for preparing magnetic liquid described in the present application, the rotation speed of the first mixing is 200-500r / min.

[0021] According to some embodiments of the method for preparing the magnetic liquid described in the present application, in step (2), the temperature of the second mixing is 25-90° C., and the time of the second mixing is 1-60 min.

[0022] According to some embodiments of the method for preparing the magnetic liquid described in the present application, the rotation speed of the second mixing is 300-500 r / min.

[0023] According to some embodiments of the method for preparing the magnetic liquid described in the present application, in step (3), the ball milling is vacuum ball milling.

[0024] According to some embodiments of the method for preparing the magnetic liquid described in the present application, the rotation speed of the ball mill is 300-600 r / min, and the time of the ball mill is 5-10 h.

[0025] According to some embodiments of the method for preparing the magnetic liquid described in the present application, the first solvent and the second solvent each independently include one or more of water, ethanol and dichloromethane.

[0026] The third aspect of the present application provides an application of the magnetic liquid described in the first aspect of the present application or the magnetic liquid obtained by the preparation method described in the second aspect of the present application in a mechanical seal, a shock absorber and a transmission device. DETAILED DESCRIPTION

[0027] Embodiments of the present invention are described in detail below. The examples of the embodiments are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0028] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0029] The embodiment of the present application provides a magnetic liquid, comprising the following raw materials by weight: 25-30 parts of rod-shaped magnetic nanoparticles, 1-4 parts of an activator, 15-20 parts of a surfactant, and 50-75 parts of a base carrier liquid. The magnetic liquid described in the present application is prepared using rod-shaped magnetic nanoparticles, has a high coercive force, can reduce the demagnetization effect, can respond to an external fluctuating magnetic field more stably, and has good stability.

[0030] In some embodiments of the present application, the rod-shaped magnetic nanoparticles include one or more of Fe3O4 nanoparticles, γ-Fe2O3 nanoparticles and MFe2Ox nanoparticles, where 2≤X≤4, and M includes one or more of Mn, Co, Ni, Cu, Cd, Pb, Sn, Ca, Sr, Ba and Mg.

[0031] In some embodiments of the present application, the activator includes one or more of carbide, nitride and silicon dioxide. The addition of the activator can improve the stability and high temperature resistance of the magnetic nanoparticles; prevent the magnetic nanoparticles from being oxidized and avoid oxidation demagnetization caused by the external environment; in addition, the addition of the activator can also provide additional surface sites to activate the magnetic nanoparticles, so that the surfactant can be more stably adsorbed on the magnetic nanoparticles.

[0032] In some embodiments of the present application, the surfactant includes a long-chain fatty acid having a carbon number greater than or equal to 10 and a short-chain fatty acid having a carbon number less than 10. The simultaneous introduction of long-chain fatty acids and short-chain fatty acids can balance the repulsive force and adsorption force between the magnetic nanoparticles, thereby improving the stability of the magnetic nanoparticles; secondly, the surfactant and the base carrier liquid are miscible, which can better disperse the magnetic nanoparticles into the base carrier liquid to form a stable magnetic liquid.

[0033] In some embodiments of the present application, the base carrier liquid includes a fat-soluble liquid.

[0034] In some embodiments of the present application, the long-chain fatty acids include one or more of oleic acid, linoleic acid, stearic acid, palmitic acid and lauric acid.

[0035] In some embodiments of the present application, the short-chain fatty acids include one or more of acetic acid, propionic acid, butyric acid and caprylic acid.

[0036] In some embodiments of the present application, the carbide includes one or more of silicon carbide, calcium carbide and carbon nanotubes.

[0037] In some embodiments of the present application, the nitride includes one or more of silicon nitride, aluminum nitride and iron nitride.

[0038] In some embodiments of the present application, the base carrier fluid includes kerosene and / or motor oil.

[0039] In some embodiments of the present application, the volume ratio of the long-chain fatty acid to the short-chain fatty acid is 1:(1-5). When the volume ratio of the long-chain fatty acid to the short-chain fatty acid is greater than 1:1, the increase in the long-chain fatty acid will lead to an increase in the repulsive force, the base carrier liquid is easy to precipitate, the magnetic liquid is unstable, and the coercive force of the magnetic liquid is reduced; when the volume ratio of the long-chain fatty acid to the short-chain fatty acid is less than 1:5, the increase in the short chain will cause the magnetic particles to easily agglomerate together, the viscosity of the magnetic liquid increases, the stability decreases, and the coercive force of the magnetic liquid is also reduced.

[0040] The present application also provides a method for preparing the magnetic liquid according to the first aspect of the present application, comprising the following steps: (1) mixing rod-shaped magnetic nanoparticles, an activator and a first solvent to obtain coated rod-shaped magnetic nanoparticles; (2) performing a second mixing of the coated rod-shaped magnetic nanoparticles, the surfactant and the second solvent described in step (1) to obtain modified rod-shaped magnetic nanoparticles; (3) The modified rod-shaped magnetic nanoparticles and a base carrier liquid are mixed and ball milled to obtain a magnetic liquid.

[0041] The magnetic liquid described in the present application introduces an activator during the preparation process, which can prevent the magnetic nanoparticles from being oxidized and avoid oxidative demagnetization caused by the external environment, while providing more surface sites for better adsorption of surfactants. In addition, during the preparation process of the magnetic liquid described in the present application, long-chain fatty acids and short-chain fatty acids simultaneously coat the magnetic nanoparticles, which helps to better disperse the magnetic nanoparticles into the base carrier liquid to form a stable magnetic liquid.

[0042] In some embodiments of the present application, the method for preparing the rod-shaped magnetic nanoparticles comprises the following steps: Select common template materials such as alumina nanofibers, polystyrene microspheres, carbon nanotubes, silica nanospheres, etc., which have certain pore structures and stability. Select 30g of alumina nanofibers, wash with 100ml of deionized water and 100ml of anhydrous ethanol to remove impurities, add 20% citric acid solution for activation, and then wash with deionized water to obtain the activated template material.

[0043] Press Fe 2+ , Fe 3+ OH -The molar ratio of FeCl3•6H2O and FeCl2•4H2O is 0.5-0.75:1:4-4.5. FeCl3•6H2O and FeCl2•4H2O are dissolved in deionized water and stirred evenly to obtain a mixed iron salt solution. The mixed iron salt solution is added to the activated template material, and then ammonia water is added; the reaction temperature is controlled to 50°C, the stirring speed is 200r / min, and the reaction time is 4h to obtain rod-shaped nanomagnetic particles; the obtained rod-shaped nanomagnetic particles are repeatedly washed with 10% NaOH solution for 3-5 times, and then repeatedly washed with deionized water until pH=7, the template and impurities are removed, and vacuum drying is performed to obtain rod-shaped magnetic nanoparticles.

[0044] In some embodiments of the present application, in step (1), the temperature of the first mixing is 25-40°C, for example, 25°C, 30°C, 35°C, 38°C, 40°C, etc., and the time of the first mixing is 1-60min, for example, 1min, 5min, 10min, 15min, 20min, 26min, 36min, 43min, 52min, 60min, etc.

[0045] In some embodiments of the present application, the rotation speed of the first mixing is 200-500r / min, for example, 200r / min, 260r / min, 320r / min, 430r / min, 500r / min, etc.

[0046] In some embodiments of the present application, in step (2), the temperature of the second mixing is 25-90°C, for example, 25°C, 35°C, 43°C, 55°C, 67°C, 78°C, 83°C, 90°C, etc., and the time of the second mixing is 1-60min, for example, 1min, 10min, 15min, 26min, 35min, 43min, 60min, etc.

[0047] In some embodiments of the present application, the rotation speed of the second mixing is 300-500r / min, for example, 300r / min, 360r / min, 430r / min, 500r / min, etc.

[0048] In some embodiments of the present application, in step (3), the ball milling is vacuum ball milling.

[0049] In some embodiments of the present application, the rotation speed of the ball mill is 300-600 r / min, and the time of the ball mill is 5-10 h, for example, 5 h, 7 h, 9 h, 10 h, etc.

[0050] In some embodiments of the present application, the first solvent and the second solvent each independently include one or more of water, ethanol and dichloromethane.

[0051] The embodiments of the present application also provide an application of the magnetic liquid described in the first aspect of the present application or the magnetic liquid obtained by the preparation method described in the second aspect of the present application in a mechanical seal, a shock absorber and a transmission device.

[0052] The technical solution of the present application is further described below in conjunction with specific embodiments.

[0053] Example 1 A method for preparing a magnetic liquid comprises the following steps: 10 g of γ-Al2O3 nanofibers were selected and washed with 50 ml of deionized water and 50 ml of anhydrous ethanol to remove impurities. The washed γ-Al2O3 nanofibers were added into 200 ml of citric acid with a mass concentration of 20% for activation treatment, and then washed with deionized water to obtain the activated γ-Al2O3 nanofiber template material.

[0054] Weigh 11g of FeCl3•6H2O and 9.7g of FeCl2•4H2O and dissolve them in 400mL of deionized water. Add the activated γ-Al2O3 nanofiber template material to the deionized water, and slowly drop 50g of concentrated ammonia water. Stir at 40°C for 3h at a stirring speed of 400r / min. It can be observed that the mixed solution quickly changes from red to black. After the reaction is completed, the magnetic particles are magnetically separated, and repeatedly washed with deionized water until the pH of the washing solution is 7. Vacuum drying obtains rod-shaped Fe3O4 magnetic nanoparticles. The obtained nanomagnetic particles are repeatedly washed with 10% NaOH solution for 3-5 times, and then repeatedly washed with deionized water until the pH is 7, the template and impurities are removed, and vacuum drying obtains rod-shaped magnetic nanoparticles.

[0055] 12g of rod-shaped magnetic nanoparticles Fe3O4 were dispersed again in 400ml of deionized water, and 1g of SiO2 powder was added to the deionized water. The mixture was stirred at 300r / min at 25°C for 30min. The stirred solution was ultrasonicated in an ultrasonic water bath for 30min and then subjected to magnetic precipitation treatment to obtain activated rod-shaped Fe3O4 magnetic nanoparticles.

[0056] The activated rod-shaped magnetic nanoparticles, 3 ml of oleic acid and 6 ml of octanoic acid were dissolved in 400 ml of deionized water, stirred at 80°C at a speed of 300 r / min for 1 hour, and then subjected to magnetic precipitation treatment. The magnetic precipitation product was repeatedly washed with deionized water until pH = 7, and vacuum dried to obtain modified rod-shaped magnetic nanoparticles.

[0057] The modified rod-shaped magnetic nanoparticles were mixed with 30 ml of kerosene and placed in a ball mill, and the mixture was mixed by ball milling for 6 hours under vacuum at a ball mill speed of 400 r / min to obtain a magnetic liquid with reduced demagnetization effect.

[0058] Example 2 A method for preparing a magnetic liquid comprises the following steps: 10 g of γ-Al2O3 nanofibers were selected and washed with 50 ml of deionized water and 50 ml of anhydrous ethanol to remove impurities. The washed γ-Al2O3 nanofibers were added into 200 ml of citric acid with a mass concentration of 20% for activation treatment, and then washed with deionized water to obtain the activated γ-Al2O3 nanofiber template material.

[0059] Weigh 11g of FeCl3•6H2O and dissolve it in 400mL of deionized water. Add the activated γ-Al2O3 nanofiber template material to the deionized water, and slowly drop 50g of concentrated ammonia water. Stir at 40°C for 3h at a stirring speed of 400r / min. It can be observed that the mixed solution quickly changes from red to black. After the reaction is completed, magnetic particles are separated by magnetism, repeatedly washed with deionized water until the pH of the washing solution is 7, and vacuum dried to obtain rod-shaped γ-Fe2O3 magnetic nanoparticles. The obtained nanomagnetic particles are repeatedly washed with 10% NaOH solution for 3-5 times, and then repeatedly washed with deionized water until the pH is 7, the template and impurities are removed, and vacuum dried to obtain rod-shaped magnetic nanoparticles.

[0060] 12g of rod-shaped magnetic nanoparticles γ-Fe2O3 were dispersed again in 400ml of deionized water, and 1g of SiO2 powder was added to the deionized water. The mixture was stirred at 300r / min at 25°C for 30min. The stirred solution was ultrasonicated in an ultrasonic water bath for 30min and then subjected to magnetic precipitation treatment to obtain activated rod-shaped γ-Fe2O3 magnetic nanoparticles.

[0061] The coated rod-shaped magnetic nanoparticles, 3 ml of oleic acid and 6 ml of octanoic acid were dissolved in 400 ml of deionized water, stirred at 80°C at a speed of 300 r / min for 1 hour, and then subjected to magnetic precipitation treatment. The magnetic precipitation product was repeatedly washed with deionized water until pH = 7, and vacuum dried to obtain modified rod-shaped magnetic nanoparticles.

[0062] The modified rod-shaped magnetic nanoparticles were mixed with 30 ml of kerosene and placed in a ball mill, and the mixture was mixed by ball milling for 6 hours under vacuum at a ball mill speed of 400 r / min to obtain a magnetic liquid with reduced demagnetization effect.

[0063] Example 3 A method for preparing a magnetic liquid comprises the following steps: 10 g of γ-Al2O3 nanofibers were selected and washed with 50 ml of deionized water and 50 ml of anhydrous ethanol to remove impurities. The washed γ-Al2O3 nanofibers were added into 200 ml of citric acid with a mass concentration of 20% for activation treatment, and then washed with deionized water to obtain the activated γ-Al2O3 nanofiber template material.

[0064] Weigh 11g of CoCl3•6H2O and dissolve it in 9.7g of FeCl2•4H2O and add it to 400mL of deionized water. Add the activated γ-Al2O3 nanofiber template material to the deionized water, and slowly drop 50g of concentrated ammonia water. Stir at 40°C for 3h at a stirring speed of 400r / min. It can be observed that the mixed solution quickly changes from red to black. After the reaction is completed, the magnetic particles are magnetically separated, and repeatedly washed with deionized water until the pH of the washing solution is 7, and vacuum dried to obtain rod-shaped Co¬Fe2O4 magnetic nanoparticles. The obtained nanomagnetic particles are repeatedly washed with 10% NaOH solution for 3-5 times, and then repeatedly washed with deionized water until the pH is 7, the template and impurities are removed, and vacuum dried to obtain rod-shaped magnetic nanoparticles.

[0065] 12g of rod-shaped magnetic nanoparticles CoFe2O4 were dispersed again in 400ml of deionized water, and 1g of SiO2 powder was added to the deionized water. The mixture was stirred at 300r / min at 25°C for 30min. The stirred solution was ultrasonicated in an ultrasonic water bath for 30min and then subjected to magnetic precipitation treatment to obtain activated rod-shaped CoFe2O4 magnetic nanoparticles.

[0066] The coated rod-shaped magnetic nanoparticles, 3 ml of oleic acid and 6 ml of octanoic acid were dissolved in 400 ml of deionized water, stirred at 80°C at a speed of 300 r / min for 1 hour, and then subjected to magnetic precipitation treatment. The magnetic precipitation product was repeatedly washed with deionized water until pH = 7, and vacuum dried to obtain modified rod-shaped magnetic nanoparticles.

[0067] The modified rod-shaped magnetic nanoparticles were mixed with 30 ml of kerosene and placed in a ball mill, and the mixture was mixed by ball milling for 6 hours under vacuum at a ball mill speed of 400 r / min to obtain a magnetic liquid with reduced demagnetization effect.

[0068] Example 4 The magnetic liquid described in Example 4 is different from that in Example 1 only in that the volume ratio of long-chain fatty acids to short-chain fatty acids in the preparation process of the magnetic liquid described in Example 4 is 1:1.

[0069] Example 5 The magnetic liquid described in Example 5 is different from that in Example 1 only in that the volume ratio of long-chain fatty acids to short-chain fatty acids in the preparation process of the magnetic liquid described in Example 5 is 1:3.

[0070] Example 6 The magnetic liquid described in Example 6 is different from that in Example 1 only in that the mass ratio of long-chain fatty acids to short-chain fatty acids in the preparation process of the magnetic liquid described in Example 6 is 1:5.

[0071] Comparative Example 1 The magnetic liquid described in Comparative Example 1 is different from that in Example 1 only in that, in the preparation process of the magnetic liquid described in Comparative Example 1, spherical magnetic nanoparticles Fe3O4 are used instead of rod-shaped magnetic nanoparticles Fe3O4.

[0072] Comparative Example 2 The magnetic liquid described in Comparative Example 2 is different from that in Example 1 only in that, during the preparation of the magnetic liquid described in Comparative Example 2, only oleic acid is used to modify the rod-shaped magnetic nanoparticles.

[0073] The specific steps include: 12g of rod-shaped magnetic nanoparticles were dispersed again in 400ml of deionized water, and 1g of SiO2 powder was added to the deionized water. The mixture was stirred at 300r / min at 25°C for 30min. The stirred solution was ultrasonicated in an ultrasonic water bath for 30min and then subjected to magnetic precipitation treatment to obtain activated rod-shaped Fe3O4 magnetic nanoparticles.

[0074] The activated rod-shaped magnetic nanoparticles and 9 ml of oleic acid were dissolved in 400 ml of deionized water, stirred at 80°C at a speed of 300 r / min for 1 hour, and then subjected to magnetic precipitation treatment. The magnetic precipitation product was repeatedly washed with deionized water until pH = 7, and vacuum dried to obtain modified rod-shaped magnetic nanoparticles.

[0075] The modified rod-shaped magnetic nanoparticles were mixed with 30 ml of kerosene and placed in a ball mill, and the mixture was mixed by ball milling for 6 hours under vacuum at a ball mill speed of 400 r / min to obtain a magnetic liquid with reduced demagnetization effect.

[0076] Comparative Example 3 The magnetic liquid described in Comparative Example 3 is different from that in Example 1 only in that, during the preparation of the magnetic liquid described in Comparative Example 3, only octanoic acid is used to modify the rod-shaped magnetic nanoparticles.

[0077] The specific steps include: 12g of rod-shaped magnetic nanoparticles Fe3O4 were dispersed again in 400ml of deionized water, and 1g of SiO2 powder was added to the deionized water. The mixture was stirred at 300r / min at 25°C for 30min. The stirred solution was ultrasonicated in an ultrasonic water bath for 30min and then subjected to magnetic precipitation treatment to obtain activated rod-shaped Fe3O4 magnetic nanoparticles.

[0078] The activated rod-shaped magnetic nanoparticles and 9 ml of octanoic acid were dissolved in 400 ml of deionized water, stirred at 80°C at 300 r / min for 1 hour, and then subjected to magnetic precipitation treatment. The magnetic precipitation product was repeatedly washed with deionized water until pH = 7, and vacuum dried to obtain modified rod-shaped magnetic nanoparticles.

[0079] The modified rod-shaped magnetic nanoparticles were mixed with 30 ml of kerosene and placed in a ball mill, and the mixture was mixed by ball milling for 6 hours under vacuum at a ball mill speed of 400 r / min to obtain a magnetic liquid with reduced demagnetization effect.

[0080] Comparative Example 4 The magnetic liquid described in Comparative Example 4 is different from that in Example 1 only in that, during the preparation of the magnetic liquid described in Comparative Example 4, only the rod-shaped magnetic nanoparticles are activated without being modified.

[0081] The specific steps include: 12g of rod-shaped magnetic nanoparticles Fe3O4 were dispersed again in 400ml of deionized water, and 1g of SiO2 powder was added to the deionized water. The mixture was stirred at 300r / min at 25°C for 30min. The stirred solution was ultrasonicated in an ultrasonic water bath for 30min and then subjected to magnetic precipitation treatment to obtain activated rod-shaped Fe3O4 magnetic nanoparticles.

[0082] The activated rod-shaped Fe3O4 magnetic nanoparticles were mixed with 30 ml of kerosene and placed in a ball mill. The mixture was vacuumed and ball milled at a speed of 400 r / min for 6 hours to obtain a magnetic liquid with reduced demagnetization effect.

[0083] The performance of the magnetic liquids described in Examples 1-6 and Comparative Examples 1-4 of the present application was studied, and the results are shown in Table 1.

[0084] Table 1

[0085] Note: The saturation magnetization and the coercive force described in this application are tested and characterized by a vibrating sample magnetometer (VSM); the stability of the magnetic liquid is characterized by placing it in a magnetic field and observing whether stratification occurs.

[0086] It can be seen from Table 1 that: through the analysis of Examples 1-3, it can be concluded that the magnetic liquid prepared using rod-shaped Fe3O4 magnetic nanoparticles, compared with the magnetic liquid prepared using γ-Fe2O3 and CoFe2O4 rod-shaped magnetic nanoparticles, exhibits higher saturation magnetization intensity and coercive force, has better magnetic properties, and has stronger anti-demagnetization characteristics.

[0087] The following conclusions can be drawn from the analysis of Example 1 and Examples 4-6: When the volume ratio of long-chain fatty acids to short-chain fatty acids is 1:2 and the ratio ranges from 1:1 to 1:5, whether increasing the content of long-chain fatty acids or increasing the content of short-chain fatty acids will lead to a decrease in the saturation magnetization and coercive force of the magnetic liquid. Therefore, by modifying the magnetic nanoparticles with a volume ratio of long-chain fatty acids to short-chain fatty acids of 1:2, a magnetic liquid with better magnetic properties and anti-demagnetization characteristics can be obtained.

[0088] The following conclusions can be drawn from the analysis of Example 1 and Comparative Example 1: The magnetic liquid prepared using rod-shaped Fe3O4 magnetic nanoparticles has a higher coercive force than the magnetic liquid prepared using spherical Fe3O4 magnetic nanoparticles, which indicates that rod-shaped magnetic nanoparticles have better anti-demagnetization properties than spherical magnetic nanoparticles.

[0089] The following conclusions can be drawn from the analysis of Example 1 and Comparative Examples 2-3: The magnetic liquid prepared by simultaneously coating magnetic particles with long-chain and short-chain fatty acids has higher saturation magnetization, coercive force and stability than the magnetic liquid prepared by modifying rod-shaped Fe3O4 magnetic nanoparticles using long-chain fatty acids or short-chain fatty acids as surfactants alone.

[0090] The following conclusions can be drawn from the analysis of Example 1 and Comparative Example 4: Only by activating the surface of magnetic nanoparticles without adding surfactants for modification, a stable magnetic liquid cannot be prepared, which leads to stratification of the magnetic liquid.

[0091] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A magnetic liquid, characterized in that: The invention comprises the following raw materials in parts by weight: 25-30 parts of rod-shaped magnetic nanoparticles, 1-4 parts of an activator, 15-20 parts of a surfactant and 50-75 parts of a base carrier liquid.

2. The magnetic liquid according to claim 1, characterized in that: The rod-shaped magnetic nanoparticles include one or more of Fe3O4 nanoparticles, γ-Fe2O3 nanoparticles and MFe2Ox nanoparticles, wherein 2≤X≤4, and M includes one or more of Mn, Co, Ni, Cu, Cd, Pb, Sn, Ca, Sr, Ba and Mg; and / or, the activator comprises one or more of carbides, nitrides and silicon dioxide; And / or, the surfactant includes a long-chain fatty acid having a carbon number greater than or equal to 10 and a short-chain fatty acid having a carbon number less than 10; And / or, the base carrier liquid comprises a fat-soluble liquid.

3. The magnetic liquid according to claim 1, characterized in that: The long-chain fatty acids include one or more of oleic acid, linoleic acid, stearic acid, palmitic acid and lauric acid; And / or, the short-chain fatty acids include one or more of acetic acid, propionic acid, butyric acid and octanoic acid; and / or, the carbide comprises one or more of silicon carbide, calcium carbide and carbon nanotubes; and / or, the nitride comprises one or more of silicon nitride, aluminum nitride and iron nitride; And / or, the base carrier fluid comprises kerosene and / or motor oil.

4. The magnetic liquid according to claim 2, characterized in that: The volume ratio of the long-chain fatty acid to the short-chain fatty acid is 1:(1-5).

5. The method for preparing the magnetic liquid according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) performing a first mixing of rod-shaped magnetic nanoparticles, an activator, and a first solvent to obtain activated rod-shaped magnetic nanoparticles; (2) performing a second mixing of the activated rod-shaped magnetic nanoparticles, the surfactant and the second solvent in step (1) to obtain modified rod-shaped magnetic nanoparticles; (3) The modified rod-shaped magnetic nanoparticles and a base carrier liquid are mixed and ball milled to obtain a magnetic liquid.

6. The method for preparing the magnetic liquid according to claim 5, characterized in that: In step (1), the temperature of the first mixing is 25-40° C., and the time of the first mixing is 1-60 min; And / or, the rotation speed of the first mixing is 200-500r / min.

7. The method for preparing the magnetic liquid according to claim 5, characterized in that: In step (2), the temperature of the second mixing is 25-90° C., and the time of the second mixing is 1-60 min; And / or, the second mixing speed is 300-500r / min.

8. The method for preparing magnetic liquid according to claim 5, characterized in that: In step (3), the ball milling is vacuum ball milling; And / or, the rotation speed of the ball mill is 300-600 r / min, and the time of the ball mill is 5-10 h.

9. The method for preparing magnetic liquid according to claim 5, characterized in that: The first solvent and the second solvent each independently include one or more of water, ethanol and dichloromethane.

10. Use of the magnetic liquid according to any one of claims 1 to 4 or the magnetic liquid obtained by the preparation method according to any one of claims 5 to 9 in mechanical seals, shock absorbers and transmission devices.

Citation Information

Patent Citations

  • Manometer magnetofluid and application thereof to purification of pollutants

    CN104319054A

  • Magnetorheological fluid and preparation method thereof

    CN106548847A

  • Magnetic liquid and preparation method thereof

    CN118116685A

  • Magnetic rheological fluid containing superfine amorphous muterial

    CN1776835A

  • Magnetorheological fluid compositions

    US20060033068A1